Serum levels of soluble urokinase plasminogen activator receptor in juvenile idiopathic arthritis: a single-center Swedish case-control study - Per Lewander; Lina Wirestam; Charlotte Dahle; Jonas Wetterö; Christopher Sjöwall (BMC, 2023)
Abstract Objectives Reliable biomarkers in the early stages of idiopathic arthritis (JIA) are scarce and the disease heterogeneity makes it clinically challenging to predict the risk of joint damage. Biomarkers with prognostic potential are warranted in order to individualize treatment and follow-up in JIA. The soluble urokinase plasminogen activator receptor (suPAR) has been reported as an easily measurable biomarker for prognosis and severity in several rheumatic diseases but it has never been studied in JIA. Methods Sera from 51 well-characterized patients with JIA and 50 age- and sex-matched control subjects were collected and stored for later analysis of suPAR. Patients were carefully followed clinically over 3 years and analysis of erythrocyte sedimentation rate, C-reactive protein, rheumatoid factor (RF) and antibodies against cyclic citrullinated peptides (anti-CCP) were analyzed as part of clinical routine. Signs of joint erosions were evaluated by radiography. Results Overall, the levels of suPAR did not differ significantly between JIA patients and controls but those with polyarticular involvement showed higher suPAR (p = 0.013). In addition, elevated suPAR were associated with joint erosions (p = 0.026). Two RF/anti-CCP negative individuals with erosions showed high levels of suPAR. Conclusions We present new data on the biomarker suPAR in JIA. Our results indicate that, apart from RF and anti-CCP, analysis of suPAR could be of additional value in assessing the risk of erosions. Analysis of suPAR early could potentially guide treatment decision-making in JIA, but our observations should be confirmed in prospective studies.